Interleukin-1 gene polymorphism in a Well-maintained periodontal patient population - Raul G. Caffesse; Antonio Manuel de la Rosa Ramírez; Manuel de la Rosa Garza (Universidade Estadual de Campinas, 2015)
Genetics is considered one of the systemic factors which modulates the host response to bacterial plaque. Individuals showing interleukin-1 gene polymorphism are more prone to develop moderate to severe periodontitis. The prevalence of genotype positive individuals has been estimated around 30% in different populations studied. We have determined a 26% prevalence in a Hispanic population. At the present, minimal information is available related to the response of genotype positive subjects to periodontal therapy. This study assessed restrospectively the response to periodontal treatment in a Hispanic population according to genotype polymorphism. 28 Hispanic subjects regularly maintained in a private practice after receiving comprehensive periodontal therapy, were tested for the interleukin-1 gene polymorphism applying the PST Genetic Test*. Full mouth gingival index, probing pocket depth and clinical attachment levels were recorded, as well as their age and smoking habit. Mean values were compared for genotype positive and negative subjects. Records were reviewed to establish an individual profile of the maintenance needs for each subject. The prevalence of genotype positive subjects was 28%. No differences were found in any of the parameters evaluated between genotype positive and negative subjects. No teeth were lost during maintenance (ranging from 4 to 30 years). However the maintenance demands of the genotype positive subjects were much more stringent, requiring shorter recall intervals, routine scaling and root planing and surgical retreatment almost on an yearly basis. Within the limits of this study it can be concluded that 1) periodontal health can be maintained after treatment in spite of genotype, and 2) genotype positive subjects require closer supervision and more surgical retreatments to achieve periodontal stability.